P52 The effect of step-down intermediate care on days lost to delayed discharge from hospital: a controlled interrupted time series analysis. (September 2018) - Levin, KA; Crighton, E
Abstract : Background: Step-Down Intermediate Care (IC) was developed in Glasgow City and implemented in November 2014. IC units act as a bridging service between hospital and home, for those deemed medically fit for discharge, but who would otherwise spend some time delayed in hospital, usually due to a lack of appropriate care, support or accommodation in the community. The aim of this study was to measure the effect of IC on days delayed. Methods: Rate of days delayed per 1000 population aged 75 years+ in Glasgow City was compared before and after onset of IC with a 6 month phase-in period, using segmented linear regression with 23-month (January 2013–November 2014) pre- and 13-month (June 2015–June 2016) post- intervention periods. Rate of delayed days for residents of Inverclyde and West Dunbartonshire (I&WD)- areas with similar high levels of deprivation, within NHS GGC, but with no IC in place – were used as a comparison group, as in April 2015 a national target was set to reduce delays. Results: Between January 2013 and November 2014 rate of days delayed in hospital increased by 41%. Rate of days delayed in I&WD was approximately half that of Glasgow at the start of the study period, however these also increased in the pre intervention period, by 33%. Rates reduced in both areas between November 2014 and June 2015. After accounting for secular changes pre-intervention, Glasgow City saw a level change of −57.66 (-60.85, –54.48) days per 1000 population with no significant change in trend, 0.35 (-0.19, 0.88). However, following adjustment for changes in I&WD, and therefore a factoring out of the new national target, the impact of IC in Glasgow City was found to be a level change of −12.56 (-17.65, –7.47) and a trend change of −0.38 (−0.73, –0.04). This is equivalent to a predicted reduction due to IC of −7.28 days delayed per 1000 popn, in June 2016, and a relative reduction of 18%. Rate of days delayed in Glasgow City continued to increase over time after the introduction of IC, though at a slower rate than if IC had not existed. Conclusion: The introduction of a national target resulted in a reduction of delayed days. After factoring out this reduction, IC was responsible for a further reduction in delayed days of 18%. The rate of days delayed continued to increase over time after the introduction of IC, though at a slower rate.